PERAN TENAGA KEPENDIDIKAN PENDIDIKAN NONFORMAL (PNF) DALAM MENINGKATKAN KUALITAS WARGA BELAJAR PENDIDIKAN BERKELANJUTAN - Anisah Basleman (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
The article discusses basic assumptions that should be considered in managing adult education. These assumptions are (1) future-oriented aims, objectives and programs, (2) formulation alternative approaches related to program design, organization of instruction, instructional process, and budget; (3) value, aesthetic-oriented programs, (4) emphasis on participants’ background and potentials. Another important aspect is the roles of educators. Among other things, they should (1) realize that they cannot do everything, (2) diagnose participants, (3) create a health, creative nonformal learning atmosphere, (4) appriciate participants’ experience, (5) be fair and communicative to each participant.